Aryl[2‐(hydroxypro‐2‐yl)cyclohyxyl]dimethylsilane: A Robust Aryl(trialkyl)silane Reagent for Nickel‐catalyzed Cross‐coupling Reactions with Aryl Tosylates. Issue 5 (16th April 2013) - Tang, Shi; Li, Shu‐Hua; Nakao, Yoshiaki; Hiyama, Tamejiro
Abstract A general route for the synthesis of an aryl(trialkyl)silane reagent, aryl[2‐(hydroxypro‐2‐yl)cyclohexyl]dimethylsilane, is demonstrated. By using a carbonate salt as an activator, the robust aryl(trialkyl)silane promotes nickel‐catalyzed aryl–aryl cross‐coupling reactions with aryl tosylates in a fluoride‐free and highly chemoselective manner. A reusable cyclic silyl ether was also quantitatively recovered.